2018
DOI: 10.1016/j.jallcom.2018.07.343
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of an Al-Zn-Mg alloy processed by ECAP and heat treatments

Abstract: An investigation was conducted to study the influence of equal-channel angular pressing (ECAP) and post-ECAP aging at 393 K for 20 h on the microstructures and tensile properties of a supersaturated Al-Zn-Mg alloy together with the effect of pre-ECAP heat treatments on the mechanical properties of the alloy after ECAP and after post-ECAP heat treatments. The results show that during ECAP processing for up to 4 passes for the supersaturated Al alloy there is a simultaneous occurrence of grain refinement, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Figure 16a shows a typical TEM micrograph of the Al phase in the ECAPed alloy, where a grain with a size of about 2 μm can be found. As reported in many ECAPed materials, the formation of such fine grains is caused by the continuous evolution of dislocations, from discrete dislocations to tangles, cells, walls, and eventually sub-grain boundaries or new grain boundaries, to achieve grain refinement caused by the sufficient imposition of strain [56,57,58]. It should be noted that due to the relatively high ECAP executive temperature (648 K), the dynamic recovery and recrystallization is presumably concurrent during the ECAP process.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 16a shows a typical TEM micrograph of the Al phase in the ECAPed alloy, where a grain with a size of about 2 μm can be found. As reported in many ECAPed materials, the formation of such fine grains is caused by the continuous evolution of dislocations, from discrete dislocations to tangles, cells, walls, and eventually sub-grain boundaries or new grain boundaries, to achieve grain refinement caused by the sufficient imposition of strain [56,57,58]. It should be noted that due to the relatively high ECAP executive temperature (648 K), the dynamic recovery and recrystallization is presumably concurrent during the ECAP process.…”
Section: Discussionmentioning
confidence: 99%
“…As generally believed, the formation of UFGs in many ECAP-processed metals results from the continuous evolution of dislocations. Sufficient input strain stimulates the discrete dislocations to form tangles, cells, walls, subgrain boundaries, and grain boundaries to finally achieve dramatic grain refinement [51][52][53][54]. Because of the high stacking-fault energy of the Al crystals, dynamic recrystallization readily occurs in the deformed Al matrix, leading to low intragranular dislocation density and restricted grain refinement [55,56].…”
Section: Effect Of Ufg Al Matrix On Accelerated Anodizing Reactionmentioning
confidence: 99%
“…Studies have shown that the above-mentioned drawbacks can be significantly ameliorated when using ultrafine-grained materials [5,6], which paves the way for the development of micro-forming technology. To date, such techniques as equal-channel angular pressing (ECAP) [7][8][9], high-pressure torsion (HPT) [10] and other methods have been developed to refine the grains to micron and submicron grains of intense plastic deformation severe plastic deformation (SPD) techniques. Among them, ECAP processing is considered to be the most promising method with bulk three-dimensional isometric grains UFG material preparation.…”
Section: Introductionmentioning
confidence: 99%